Polisemi : Tomeru「とめる」 - Ariani Tanjung (Fakultas Bahasa dan Seni UNP, 2010)
The definition of the relation of meaning is the semantic relationships that exist between one language and another language. The units of this language can be words, phrases, or sentences, and semantic relationships that can express the similarity of meaning, the conflict of meaning, inclusion of meaning, duality of meaning, or also the excess of meaning. The discussion of meaning relationships is usually about some issues like synonyms, antonyms, homonymy, hyponymy, ambiguity, and redundancy. Key words: Polysemi, Tomeru [止める、停める、泊める、留める]